Postoperative change in Gleason score of prostate cancer in fusion targeted biopsy: a matched pair analysis. (2nd January 2021) - Apfelbeck, M.; Tritschler, S.; Clevert, D.-A.; Buchner, A.; Chaloupka, M.; Kretschmer, A.; Herlemann, A.; Stief, C.; Schlenker, B.
Abstract: Objective: To evaluate if MRI/ultrasound fusion based targeted biopsy (FBx) leads to a reduced rate of change in Gleason score (GS) compared to prostatectomy specimen. Methods: The histopathological findings of the biopsy of the prostate and the radical prostatectomy (RP) specimen of 210 patients who were referred to our hospital between 2012 and 2017 were compared retrospectively in this study. One hundred and five patients who underwent FBx combined with ultrasound-guided 12-core biopsy of the prostate (SBx) were matched with 105 patients who underwent SBx only. This study evaluated the rate of up- or downgrading in the RP specimen in both groups and compared the results via matched pair analysis. Results: Concordance in Gleason grade group (GGG) was found in 52/105 patients (49.5%) in SBx and in 49/105 patients (46.7%) with FBx ( p  = 0.679). The rate of downgrading was statistically significant ( p  = 0.014) and was higher in the FBx group (14/105 patients, 13.3%) than in the SBx group (4/105 patients, 3.8%). A higher rate of upgrading was seen in SBx (49/105 patients; 46.7%) compared to FBx (42/105 patients; 40%), with no statistical significance ( p  = 0.331). The change in GGG from biopsy to final pathology in patients with GGG 1 and 2 at biopsy level was not statistically significant ( p  = 0.168). Conclusion: FBx does not decrease the rate of upgrading between biopsy and final pathology in RP specimens. Our results indicate that FBx tends to overestimate the final GGG compared to SBx.